Triiodothyronin (T3) as a parameter of mortality in sepsis patients in the PICU - Sri Wahyuni Djoko; Nyoman Budi Hartawan; Bagus Ngurah Putu Arhana; Eka Gunawijaya; Anak Agung Ngurah Ketut Putra Widnyana; Dyah Kanya Wati (Indonesian Pediatric Society, 2019)
Background Thyroid hormone stimulates the regulation of β-adrenergic receptors in order to increase the inotropic effect of the heart myocardium. Euthyroid sick syndrome is a disorder of non-metabolic thyroid function, which is characterized by a decrease in triiodothyronine (T3) levels in patients with non-thyroid systemic disease, such as sepsis. Low serum T3 hormone level is a potentially high-risk factor for mortality from sepsis. Objective To assess for a relationship between decreased serum T3 levels and mortality in pediatric sepsis patients admitted in the PICU. Methods This study used a nested case-control design. The subjects were children aged 1 month-18 years who were diagnosed with sepsis in the pediatric intensive care unit at Sanglah Hospital, Denpasar, Bali, from September 2017 to January 2019. Results A total of 90 children were included, of whom 44 died and 46 survived. Median age was 10.5 (IQR 44) months in subjects who died and 9 (IQR 50) months in those who survived. The majority of subjects in both groups had well-nourished nutritional status. Bivariate analysis revealed that significantly more subjects who died had low serum T3 (≤1 ng/dL), PELOD-2 score ≥5, than subjects who survived. Multivariate analysis revealed that serum T3 £1 ng/dL (OR 55.1; 95%CI 9 to 334.8; P<0.001) and PELOD-2 score ³5 (OR 6.5; 95%CI 1.6 to 26.7; P=0.01) were significant risk factors for sepsis mortality. Conclusion Low serum T3 level and high PELOD-2 score are risk factors for death in sepsis.